Γ–radiolytic degradation of rosuvastatin in the air–saturated aqueous solution. (July 2023) - Mandić, Leo; Pocrnić, Marijana; Galić, Nives; Mihaljević, Branka; Džeba, Iva
Abstract: Widespread environmental occurrence and persistence of pharmaceuticals have attracted great concern due to their incomplete removal by conventional wastewater treatment technologies. The use of radiation technology has proven to be a good and successful alternative where highly reactive species lead to high degradation level of pharmaceuticals. Among the most commonly prescribed pharmaceuticals is rosuvastatin (ROSU), cholesterol-lowering agent, which has been detected as a contaminant in wastewater and natural waters. The aim of the present study was to investigate the γ -radiolytic degradation of ROSU in aqueous solutions under different conditions. The focus was given to the most applicable conditions, the degradation of ROSU in air, where dominant reactions of OH radicals with ROSU are expected. Therefore, the reaction rate constant of ROSU with OH radicals (2.15 ± 0.07 × 10 10  M −1  s −1 ) was determined by laser flash photolysis. By combined γ -radiolysis and mass spectrometry study, the reaction mechanism of radiation degradation of ROSU was proposed and the radiolytic products were identified. Highlights: The ROSU degradation in aqueous solutions in air was efficiently achieved at 1 kGy. The rate constant of the reaction of ROSU and OH radicals was determined. The main radiolytic products of ROSU samples irradiated in air were identified.